Thoracic surgery may alter body static balance via diaphragm dysfunction. - Janusz Kocjan; Bożena Gzik-Zroska; Katarzyna Nowakowska-Lipiec; Michał Burkacki; Sławomir Suchoń; Robert Michnik; Damian Czyżewski; Mariusz Adamek (PLoS ONE)
Many diseases and conditions can alter an ability to maintain body balance. The aim of the present study was to investigate whether thoracic surgery may elicit diaphragm dysfunction thereby impairing postural stability. 40 patients qualified to video-assisted thoracoscopy (VATS) lobectomy or lobectomy via thoracotomy due to pulmonary carcinoma were examined two times: a day before lung resection and 3-5 days after surgical procedure. Diaphragm assessment was performed using ultrasonography, while postural sways were evaluated by Zebris FDM-S stabilometric platform. Thoracic surgery was associated with decrease of diaphragm thickness and movement, as well as, with deterioration of static body balance maintenance. Upper lobe resection was linked with greater diaphragm excursion restriction and worse body sway parameters than middle and lower lobe resection. VATS lobectomy was associated with better postoperative diaphragm function and better postural sway parameters than lobectomy via thoracotomy. Patients after lobectomy via thoracotomy had significantly more load on lower limb on the operated side than patients after VATS lobectomy. Impairment of diaphragm function is closely associated with equilibrium impairment after pulmonary resection. VATS lobectomy was less invasive than lobectomy via thoracotomy in terms of primary respiratory muscle function and body balance maintenance parameters.